Robust quantum spin liquid state in the presence of giant magnetic isotope effect in D3LiIr2O6 - T. Takayama; A. S. Gibbs; K. Kitagawa; Y. Matsumoto; K. Ishii; A. Kato; R. Takano; S. Bette; R. Dinnebier; H. Takagi (npj Quantum Materials)
Abstract The deuterium isotope effect on the honeycomb iridate H3LiIr2O6, a quantum spin-orbit-entangled liquid, was examined by synthesizing D3LiIr2O6. The structural refinements indicate the different character of the interlayer OH and OD bonds, which results in a giant isotope effect on the magnetic interactions; the antiferromagnetic Curie-Weiss temperature |θ CW| of D3LiIr2O6 increases to ~ 170 K from ~ 100 K of H3LiIr2O6. Nevertheless, the quantum liquid state is robust against the deuterium isotope exchange in contrast to the theoretical prediction that the Kitaev spin liquid is stable only for a limited phase space of magnetic interactions. The bond- and site disorders associated with disordered OD(H) bonds, in combination with Kitaev physics, may play a role in realizing the quantum liquid state.